Pembangunan Kakas Bantu untuk Memprediksi Failure Rate dari Perangkat Lunak menggunakan Musa's Algorithm - Dindy Fitriannora; Bayu Priyambadha; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Software development cycle has many phases and software will undergo one of these phases, namely the testing phase where unit of program or program will be tested before being given to client to ensure the software already has things that match the needs that have been defined and each unit is in accordance with its specifications. Moreover, purpose of the testing phase is to find program defects before use. Ability of software to maintain its performance level under specified conditions for a time period is called reliability. Measurement of software reliability is centered on failures and failure intensity where failure intensity is the number of occurrences of failure in a certain time period. Failure intensity can be seen from predictable failure rates with many techniques, one of which is Musa 's algorithm that can be used at the start of testing. This system has been tested using the white box testing method with basis path testing techniques in unit testing and integration testing and black box testing methods in validation testing. This system has an accuracy rate of 100% and the duration to calculate the failure rate using the system is an average of 2000 times faster than manual calculation.